2007
DOI: 10.3732/ajb.94.11.1890
|View full text |Cite
|
Sign up to set email alerts
|

Ascoma development and phylogeny of an apothecioid dothideomycete, Catinella olivacea

Abstract: Catinella olivacea is a discomycetous fungus often found fruiting within cavities in rotting logs. Because this habitat would lack the air currents upon which discomycete species normally rely for the dispersal of their forcibly ejected ascospores, we suspected an alternative disseminative strategy might be employed by this species. An examination of the development of the discomycetous ascomata in pure culture, on wood blocks, and on agar showed that the epithecium was gelatinous at maturity and entrapped rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We also included Catinella olivacea, a discomycetous fungus that grows on rotting logs. Catinella olivacea earlier was placed in the Leotiomycetes based on the morphology, but a more recent study by Greif et al (2007) suggests that it is closely related to the Dothideomycetes, where it remains incertae sedis at the ordinal and familial rank. Results of the combined 83 taxa, two-gene (SSU + LSU) phylogeny suggested that the Minutisphaera clade did not share phylogenetic affinities with either members of Patellariaceae or C. olivacea (FIG.…”
Section: Discussionmentioning
confidence: 99%
“…We also included Catinella olivacea, a discomycetous fungus that grows on rotting logs. Catinella olivacea earlier was placed in the Leotiomycetes based on the morphology, but a more recent study by Greif et al (2007) suggests that it is closely related to the Dothideomycetes, where it remains incertae sedis at the ordinal and familial rank. Results of the combined 83 taxa, two-gene (SSU + LSU) phylogeny suggested that the Minutisphaera clade did not share phylogenetic affinities with either members of Patellariaceae or C. olivacea (FIG.…”
Section: Discussionmentioning
confidence: 99%
“…It is placed in Lecanoromycetes incertae sedis. Greif et al (2007) presented evidence from ascomal ontogeny and nuclear ribosomal DNA data that this genus, previously placed in Dermateaceae, belongs in Dothideomy-cetes. The ordinal placement could not be resolved and it is regarded as Dothideomycetes incertae sedis.…”
Section: To Accommodatementioning
confidence: 98%
“…To construct the phylogenetic tree, the analysis was modified from Greif et al (2007), instead of using two taxa, Orbilia auricolor and Scutellinia scutellata as outgroup, only O. auricolor was employed. The sequence data of the Siamese Jelly-ball were aligned by ClustalX2 with sequences of 60 species retrieved from GenBank (www.ncbi.nlm.nih.gov) representing different classes of ascomycete fungi, including Arthoniomycetes , Dothideomycetes , Eurotiomycetes , Le-canoromycetes , Leotiomycetes , Lichinomycetes, and Sor-dariomycetes, where both SSU and LSU sequences data were available (Table 2), and manually edited by MEGA 5.05.…”
Section: Methodsmentioning
confidence: 99%